AAZTA5/AAZTA5-TOC: synthesis and radiochemical evaluation with 68Ga, 44Sc and 177Lu - Jean-Philippe Sinnes; Johannes Nagel; Frank Rösch (SpringerOpen, 2019)
Abstract Purpose AAZTA (1,4-bis (carboxymethyl)-6-[bis (carboxymethyl)]amino-6-methylperhydro-1,4-diazepine) based chelators were initially developed in the context of magnetic resonance imaging. First radiochemical studies showed the capability of AAZTA to form stable complexes with radiolanthanides and moderately stable complexes with 68Ga. For a systematic comparison of the labelling capabilities with current diagnostic and therapeutic trivalent radiometals, AAZTA5 (1,4-bis (carboxymethyl)-6-[bis (carboxymethyl)]amino-6-[pentanoic-acid]perhydro-1,4-diazepine) was synthesized representing a bifunctional version with a pentanoic acid at the carbon-6 atom. To evaluate the effect of adding a targeting vector (TV) to the bifunctional chelator on the complex formation, AAZTA5-TOC was synthesized, radiolabeled and tested in comparison to the uncoupled AAZTA5. Methods AAZTA5 was synthesized in a 5-step synthesis. It was coupled to the cyclic peptide TOC (Phe1-Tyr3 octreotide) via amide bound formation. AAZTA and AAZTA5-TOC complex formations with 68Ga, 44Sc and 177Lu were investigated at different pH, temperature and precursor amounts. Stability studies against human serum, PBS buffer, EDTA and DTPA were performed. Results AAZTA5 and AAZTA5-TOC achieved quantitative labelling (> 95%) at room temperature in less than 5 min with all three nuclides at pH ranges from 4 to 5.5 with low precursor amounts of 1 to 10 nmol. [44Sc]Sc-AAZTA5 complexes as well as [44Sc]Sc-AAZTA5-TOC were completely stable. The 177Lu complexes of AAZTA5 and AAZTA5-TOC showed high stability comparable to the 44Sc complexes. In contrast, the [68Ga]Ga-AAZTA5 complex stability was rather low, but interestingly, [68Ga]Ga-AAZTA5-TOC was completely stable. Conclusion AAZTA5 appears to be a promising bifunctional chelator for 68Ga, 44Sc and 177Lu with outstanding labelling capabilities at room temperature. Complex stabilities are high in the case of 44Sc and 177Lu. While [68Ga]Ga-AAZTA complexes alone lacking stability, [68Ga]Ga-AAZTA5-TOC demonstrated high stability. The latter indicates an interesting feature of [68Ga]Ga-AAZTA5-labelled radiopharmaceuticals.